2012
DOI: 10.1002/jbm.a.34248
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of gelatin‐based biocompatible porous composite scaffold for bone tissue engineering

Abstract: In this study, composite scaffolds were prepared with polyethylene oxide (PEO)-linked gelatin and tricalcium phosphate (TCP). Chitosan, a positively charged polysaccharide, was introduced into the scaffolds to improve the properties of the artificial bone matrix. The chemical and thermal properties of composite scaffolds were investigated by Fourier transform infrared spectroscopy, thermogravimetric analyzer, differential thermal analyzer. In vitro cytotoxicity of the composite scaffold was also evaluated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Five samples per each time point were prepared in cylinder shape of approximately 6 mm in diameter and 12 mm in height in accordance with ASTM F 451–95 [26], all the calculations were done assuming that the section area of specimens remain unchanged during the test. Each Specimen was immersed into 1mL of α-MEM before the test.…”
Section: Methodsmentioning
confidence: 99%
“…Five samples per each time point were prepared in cylinder shape of approximately 6 mm in diameter and 12 mm in height in accordance with ASTM F 451–95 [26], all the calculations were done assuming that the section area of specimens remain unchanged during the test. Each Specimen was immersed into 1mL of α-MEM before the test.…”
Section: Methodsmentioning
confidence: 99%
“…However, when compared to the CH scaffolds, a statistically significant decrease in porosity was observed after the addition of β-TCP to the scaffold composition. Previous studies have shown that the porosity decreases with the increasing of ceramic particle content, since an increase in the density of the scaffold is verified [66]. In addition, the pore size of the scaffolds was further characterized by SEM analysis.…”
Section: Total Porosity Evaluationmentioning
confidence: 99%
“…This functionality helps to determine anti tumor and chemotherapeutic agents [14]. In the study, it was found that, Pomelo has a very strong cytotoxic property with 100% mortality rate.…”
Section: Figure 8 Total Phenolics Contents Of the Samples (Mg Gae/g)mentioning
confidence: 99%
“…Vitamin C, Protein and Iron Content In vitro Cytotoxicity Test was performed using Brine Shrimp Lethality Bioassay method as described previously [14]. Previous method for Raw and fresh samples was also used to determine Vitamin C by HPLC [15].…”
Section: Determination Of Cytotoxic Property Andmentioning
confidence: 99%